Case Report: Primary Indolent Epstein-Barr Virus-Positive T-Cell Lymphoproliferative Disease Involving the Central Nervous System - Wang, Kun; Li, Jinjian; Zhou, Xuehui; Lv, Junhui; Wang, Yirong; Li, Xinwei (Frontiers in Surgery, 2022)
Background T-cell lymphoproliferative disease (T-LPD), characterized by primary Epstein-Barr virus (EBV) infection and clonal proliferation of T cells, occurs both in systemic and non-lymphatic organs. However, isolated indolent EBV-positive T-LPD involving the central nervous system was rarely reported. Case presentation A 48-year-old male was admitted to our department, who complained of headache, blurred vision and weakness of left lower limb for one month. Neither neurological deficit nor palpable lymphadenopathy was found. Bone marrow and laboratory tests showed no abnormality. Enhanced magnetic resonance imaging (MRI) demonstrated enhanced cotton-like lesions up to 20 mm in diameter, located in the right frontal, temporal, parietal and left parietal, occipital lobes with perifocal edema. And the neuronavigation-assisted mini-craniotomy was performed to achieve a total excision of the right temporal superficial lesion and identify the diagnosis. Pathological and EBV analysis described the lesion as indolent EBV-positive T-cell lymphoproliferative disease of the central nervous system. Then the therapeutic regimen including whole-brain irradiation, chemotherapy, prednisolone and aciclovir was given. Serial radiological imaging showed no signal of recurrence at a five months’ follow-up. Conclusion Primary indolent T-LPD in the central nervous system is quite rare, which needs to be distinguished from aggressive cerebral T-cell lymphoma, metastatic tumors and other CNS lesions.